The role of the planar cell polarity pathway in branching morphogenesis - Yates, L; Laura Yates (2011)
The development of organs such as the lung and kidney occurs by branching morphogenesis. Changes in the cytoskeletal architecture, cell-cell adhesion and cell polarity are necessary for the formation of new branches. Interactions and reciprocal signalling between epithelial and mesenchymal cells mediate these organised cell movements that give rise to a complex system of tubes suitable for the transport of gas or fluids. Mutations that disrupt formation of either the correct number, or shape of epithelial branches, affect lung function. This, in turn, can lead to congenital abnormalities such as cystadenomatoid malformations, pulmonary hypertension or lung hypoplasia. Defects in lung architecture are also associated with adult lung disease, particularly in cases of idiopathic lung ﬁbrosis. Identifying the signaling pathways that drive epithelial tube formation will likely shed light on both congenital and adult lung disease. This study shows that mutations in the planar cell polarity (PCP) genes: Celsr1; Vangl2 and Scribble, lead to disrupted lung development and defects in lung architecture. Examination of Vangl2 mutant kidneys reveals similar impairment of branching morphogenesis. Detailed histological and immunocytochemical analysis reveals that lungs from Celsr1Crsh/Crsh, Vangl2Lp/Lp and ScribbleCrc/Crc mice are small and misshapen with fewer branches, and by late gestation exhibit thickened interstitial mesenchyme and defective saccular formation. Moreover, epithelial integrity is disrupted, cytoskeletal remodeling perturbed and mutant endoderm does not branch normally in response to the chemoattractant FGF10. In ex-vivo culture, inhibition of Rho kinase, an important downstream effector of the PCP signaling pathway, can mimic the branching defects observed in these three mouse mutants. Furthermore, all three proteins are present in restricted spatial domains within lung epithelium. ScribbleCrc/Crc lungs, the most severely affected line, exhibit additional defects in components of the tight and adherens junctions; this in turn affects lumen diameter. These findings show that components of the PCP pathway: Celsr1; Vangl2 and Scribble are required for normal foetal lung development, thereby revealing a novel signalling pathway critical for this process. Examination of postnatal mice was not possible as homozygous mutations result in embryonic lethality. However, an assessment of Vangl2Lp/+ mice reveals that loss of a single copy of Vangl2 is enough to cause defects in embryonic lung development that persist into adult life, affecting lung function. Similarly, Vangl2Lp/+ mice show a small but significant reduction in kidney glomeruli.